Spider (Araneae) and harvestman (Opiliones) communities are structured by the ecosystem engineering of burrowing mammals. Issue 3 (30th September 2019) - Lindtner, Peter; Gajdoš, Peter; Stašiov, Slavomír; Čiliak, Marek; Pech, Pavel; Kubovčík, Vladimír
Abstract: Burrowing mammals through their digging activities are important ecosystem engineers and bioturbators in grassland ecosystems. Through habitat formation, they can have significant effects on other species in an ecosystem, structuring their abundance and diversity. We analysed the effect of the European ground squirrel ( Spermophilus citellus ) on spider (Araneae) and harvestman (Opiliones) communities, because these arachnids are the most abundant and dominant predators with a great variety of foraging strategies, and their community composition is strongly influenced by the physical structure of the environment. We established replicate mound plots positioned directly in the centre of ground squirrel mounds with paired off‐mound control plots undisturbed by ground squirrels. We sampled spiders and harvestmen using pitfall traps on 30 ground squirrel mounds and 30 paired off‐mound control plots at two study sites differing in grazing intensity and plant species richness. We found that the response of spiders was site‐specific, while harvestmen responded consistently to disturbances by burrowing mammals. Mounds exhibited increased abundance and species richness of harvestmen at both study sites, while species richness of spiders was increased only in intensively managed grassland. We also detected compositional changes of the arachnid community on the mounds in comparison to the grassland matrix. Our findings indicate that burrowing mammals through physical state changes in abiotic and biotic material modulate the resources for other species and maintain a high diversity of biotic communities in intensively grazed grasslands. Abstract : Ecosystem engineering of burrowing mammals significantly influenced spider and harvestman community; however, spiders and harvestmen responded differently. The effect of burrowing mammals on spider abundance and species richness was site‐specific, while the effect on harvestmen was consistent at study sites. The activities of burrowing mammals can structure species and guild composition of arachnid communities in temperate grasslands.